MENINGKATKAN KEMAMPUAN MENGENAL WARNA MELALUI MEDIA PASIR BERWARNA BAGI ANAK TUNAGRAHITA RINGAN - Hasnah - Khairani (Universitas Negeri Padang, 2013)
This research early from perception which is researcher execute in SLB Fan Redha Padang. Researcher find a child of intelegance belowof ability resistance recognize colour that is ruddling, colour turn yellow and green colour. The disability correlateto ability in mentioning colour, showing colour and sort colour. This pursuabt to research the mentioned aim to be ability recognize child colour can be improved. Media which is used in this research is chromatic sand painting media. This research use approach of experiment in the form of Single Subject Research (SSR) using desain A and B. Subjek research is a child of intelegence below. Goals of Behavior is ability of child in recognizing colour (mentioning, showing and sorting) precisely and correctness. Result of this research of showing that ability recognize colour at child of intelegence below. At condition of beseline on first until third day not yet earned to recognize colour, on 4 ability of child recognize colour 22,2%, at day to 5 ability of child recognize colour 22,2%, and day to 6 ability of child recognize colour 22,2%. At condition of day intervention 7 given by treatment pass activity paste up chromatic sand at picture wake up to level off triangle ability of child 22,2%, on 8 ability of child 22,2%, day 9 ability of child 33,3%, day 10 ability of child 66,6%, on 11 ability of child 77,7%, and on 12 ability of child 99,9%, on to 13 ability of child 99,9% and day to 14 ability of child 99,9. Pursuant to result of research of activity paste up chromatic sand at picture wake up to level off triangle by repeatedly can improve ability recognize colour with chromatic sand painting media at child of intelegence below in class of D II/ C SLB Fan Redha Field. Researcher Suggest to researcher and teacher here in after so that can use chromatic sand to increase ability recognize colour at child of intelegence below.